Mapping the metagenomic diversity of the multi-kingdom glacier-fed stream microbiome - Michoud, Grégoire; Peter, Hannes; Busi, Susheel Bhanu; Bourquin, Massimo; Kohler, Tyler J; Geers, Aileen; Ezzat, Leila; Vanishing Glaciers Field Team; Battin, Tom J (Nature microbiology, 2025)
Glacier-fed streams (GFS) feature among Earth's most extreme aquatic ecosystems marked by pronounced oligotrophy and environmental fluctuations. Microorganisms mainly organize in biofilms within them, but how they cope with such conditions is unknown. Here, leveraging 156 metagenomes from the Vanishing Glaciers project obtained from sediment samples in GFS from 9 mountains ranges, we report thousands of metagenome-assembled genomes (MAGs) encompassing prokaryotes, algae, fungi and viruses, that shed light on biotic interactions within glacier-fed stream biofilms. A total of 2,855 bacterial MAGs were characterized by diverse strategies to exploit inorganic and organic energy sources, in part via functional redundancy and mixotrophy. We show that biofilms probably become more complex and switch from chemoautotrophy to heterotrophy as algal biomass increases in GFS owing to glacier shrinkage. Our MAG compendium sheds light on the success of microbial life in GFS and provides a resource for future research on a microbiome potentially impacted by climate change.
Keywords: ledový příkrov; geologické sedimenty; viry; Metagenome; Viruses; Ice Cover; Bacteria; biofilmy; metagenomika; Biofilms; Fungi; Geologic Sediments; Metagenomics; Biodiversity; houby; mikrobiota; ekosystém; Microbiota; Rivers; biodiverzita; řeky; metagenom; Ecosystem